2015
DOI: 10.1080/15323269.2015.982007
|View full text |Cite
|
Sign up to set email alerts
|

CampusGuides: A Solution for the Hospital Library

Abstract: Our large nonprofit health system consists of one main campus and several regional hospitals, each with varying degrees of library services, access, and staffing. When our free wiki-based Web site platform went down unexpectedly, we needed a quick solution for our library Web pages. This article details our transition to LibGuides content management system (CMS; formerly called CampusGuides). Library Web sites across the hospital system now have a much more consistent "look & feel," are easier to update, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…However, since then, all three have been discontinued or replaced by other software (Boeninger 2011). Woody (2015, 1-12) describes a case study of a multi-site hospital library that migrated from freely-hosted wiki software for the library website to LibGuides CMS. Surveying use of Web 2.0 tools in 120 public and academic libraries, Chua and Goh found that wikis were only used in ten of those libraries, primarily for collecting subject-matter related material (2010,208).…”
Section: Wikis and Subject Guidesmentioning
confidence: 99%
“…However, since then, all three have been discontinued or replaced by other software (Boeninger 2011). Woody (2015, 1-12) describes a case study of a multi-site hospital library that migrated from freely-hosted wiki software for the library website to LibGuides CMS. Surveying use of Web 2.0 tools in 120 public and academic libraries, Chua and Goh found that wikis were only used in ten of those libraries, primarily for collecting subject-matter related material (2010,208).…”
Section: Wikis and Subject Guidesmentioning
confidence: 99%